Characterization of the Intestinal Microbiota of Broiler Breeders With Different Egg Laying Rate - Yang, Zengqiao; Zhang, Chunhua; Wang, Jianping; Celi, Pietro; Ding, Xuemei; Bai, Shiping; Zeng, Qiufeng; Mao, Xiangbing; Zhuo, Yong; Xu, Shengyu; Yan, Hui; Zhang, Keying; et al. (Frontiers in Veterinary Science, 2020)
The gastrointestinal microbiota plays a pivotal role in maintaining animal health, immunity and reproductive performances. However, literature about the relationship between microbiota and reproductive performance is limited. The aim of the present study was to determine differences in the intestinal microbiota of broiler breeders with different egg laying rate. A total of 200 AA+ parent broiler breeders (41-week-old) were separated into two groups according to their different egg laying rate [average egg laying rate group (AR: 78.57 ± 0.20%) and high egg laying rate group (HR: 90.79 ± 0.43%). Feed conversion ratio (FCR), ovary cell apoptosis rate (ApoCR) and relative abdominal fat weight were lower (p = 0.01), while the hatchability rate of qualified egg was higher (p = 0.04) in HR group than that in AR group. Phascolarctobacterium abundance were lower (p = 0.012) in ileum of HR birds. Romboutsia (genus) in ileum was negatively related to the feed efficiency (r = −0.58, p < 0.05), Firmicutes (phylum) and Lactobacillus (genus) abundances in cecum were positively related to the egg laying rate (ELR) (r = 0.35 and 0.48, p < 0.05), feed efficiency (r = 0.42 and 0.43, p < 0.05), while Spirochaetes (phylum) and Sphaerochaeta (genus) abundances in cecum were negatively related to the ELR (r = −0.43 and −0.70, p < 0.05), feed efficiency (r = 0.54 and 0.48, p < 0.05), and positively related to ApoCR (r = 0.46 and 0.47, p < 0.05). Our results suggested that microbiota, such as Firmicutes (phylum) and Lactobacillus (genus) have positive relationship, while Spirochaetes (phylum) and Romboutsia (genus) abundances exert negative relationship with broiler breeders' reproductive performances.